Spinal Subdural Hematoma Associated with Intracranial Subdural Hematoma - Kim, Myoung Soo (J Korean Neurosurg Soc, 2015)
The simultaneous occurrence of an intracranial and a spinal subdural hematoma (SDH) is rare. We describe a case of cranial SDH with a simultaneous spinal SDH. An 82-year-old woman visited the emergency room because of drowsiness and not being able to walk 6 weeks after falling down. A neurological examination showed a drowsy mentality. Brain computed tomography showed bilateral chronic SDH with an acute component. The patient underwent an emergency burr-hole trephination and hematoma removal. She exhibited good recovery after the operation. On the fourth postoperative day, she complained of low-back pain radiating to both lower limbs, and subjective weakness of the lower limbs. Spine magnetic resonance imaging revealed a thoracolumbosacral SDH. A follow-up spinal magnetic resonance imaging study that was performed 16 days later showed a significant decrease in the size of the spinal SDH. We discuss the pathogenesis of this simultaneous occurrence of spinal and cranial SDH.